ACCEPTABILITY OF SUPPLEMENTS TO THE AIR CODE OF UKRAINE - Миронець, О. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
This article presents the research and analysis of the conceptual apparatus of air travel. Proposed aspects to which the legislator ought to pay attention to the construction standards of the Air Code of Ukraine in the new version under "Air transport" and "Responsibility for violation of legislation regulating the use of airspace Ukraine".